Sphincter of Oddi laxity alters bile duct microbiota and contributes to the recurrence of choledocholithiasis - Zhang, Qi (Ann Transl Med, 2020)
BACKGROUND: Choledocholithiasis is closely associated with bacterial infection and inflammation in the bile duct. Our previous studies showed that sphincter of Oddi laxity (SOL) significantly altered the bile microbiota and might contribute to the recurrence of biliary stones. However, the direct association among SOL, the bile microbiota, and choledocholithiasis recurrence is unclear. METHODS: We prospectively recruited 202 patients with choledocholithiasis, and obtained bile samples from the common bile duct. We performed 16S ribosomal RNA gene analysis to characterize the bile microbiota and analyzed the risk factors for choledocholithiasis. RESULTS: Distinct bile microbial communities were identified in patients with and without SOL, with a significantly larger abundance of Rhizobiaceae in patients with SOL. Patients with SOL had a higher risk of biliary stone recurrence, with a considerably shorter recurrence time. The abundance of Clostridium was significantly higher in patients with stone recurrence. SOL [P=0.024, hazard ratio (HR) =10.800, 95% confidence interval (CI): 1.377–84.701] was an independent risk factor of choledocholithiasis recurrence. CONCLUSIONS: Choledocholithiasis patients with and without SOL demonstrated significant differences in their microbial communities. SOL is a critical risk factor for the recurrence of choledocholithiasis after surgery. The presence of Clostridium may be potentially associated with the recurrence of SOL-induced choledocholithiasis.